PRESENTING WOMEN IN POST-INDEPENDENCE HISTORIOGRAPHY: BUILDING THE CHARACTER OF STATE DEFENSE THROUGH THE HISTORY - Wulandari, Ayu (Jurnal Pertahanan dan Bela Negara, 2020)
This paper discusses the importance of historical narrative in an effort to grow the character of the defense of the country. This is motivated by the problem of mindset about defending the country, that defending the country is the duty of the Indonesian National Army and Police, and defending the country is only appropriate for men. In this issue, historical studies play an important role in deconstructing people’s mindsets. Therefore, this paper offers a solution to build the character of state defense, namely through efforts to present women in post-independence historiography. This paper aims to encourage the dismantling of the exclusion of women’s roles in post-independence historiography, because in reality, Indonesian women are involved in the defense of the state after 1945. The results of the research in this paper show that after Indonesia’s independence, many women had a role important in politics, the arts, to the health sector. By introducing a narrative about how important the role of women in the history of post-independence, the younger generation will have an awareness that defending the country can also be done by women. Thus, presenting women in post-independence historiography will greatly help the Indonesian people to grow the character of state defense. Keywords: Exclusion, Historical Awareness, Historiography, State Defense, Women.